Effect of steam-assisted alkaline pretreatment plus enzymolysis on converting corn stalk into reducing sugar. (October 2020) - Liu, Chaoqi; Liu, Mengjie; Wang, Ping; Chang, Juan; Yin, Qingqiang; Zhu, Qun; Lu, Fushan
Abstract: In order to improve corn stalk conversion into total reducing sugar effectively, steam-assisted alkaline pretreatment and enzymatic hydrolysis was studied. This result showed that cellulose and hemicelluloses contents in corn stalk were decreased to 7.01% and 4.41% ( P  < 0.05), and total reducing sugar yield was increased to 335.09 mg/g biomass ( P  < 0.05), when corn stalk was pretreated with steam and alkali (0.8% NaOH + 1.2% CaO, W/V) for 1.0 h at a ratio of alkaline solution to corn stalk of 5:1 (V/W), followed by enzymatic hydrolysis at 22.5 FPU/g biomass cellulase for 48 h. The synthetical enzymatic hydrolysis conditions of pretreated corn stalk were pH 5.0, 50 °C, 60 filter paper unit (FPU)/g biomass and 48 h reaction time, in which total reducing sugar yield was 358.97 mg/g biomass ( P  < 0.05). The further response-surface methodology results showed that the total reducing sugar reached 493.74 mg/g biomass under the conditions of 52.39 FPU/g biomass cellulase, 6599.99 U/g biomass β-glucanase and 40 h reaction time. Scanning electron microscopy (SEM), X-ray diffraction (XRD) and pore structure analyses indicated that steam-assisted alkaline pretreatment plus enzymatic hydrolysis were effective in breaking the crystal structure of corn stalk for increasing total reducing sugar yield. Highlights: Steam-assisted alkaline pretreatment broke down crystal structure of corn stalk. Physiochemical pretreatment increased hemicellulose degradation rates. Enzymatic hydrolysis conditions were optimized by central composite design. Cellulose and hemicelluose contents were decreased by enzymolysis. Reducing sugar yield was increased by physiochemical pretreatment plus enzymolysis.